Spatiotemporal Analysis of Circulation Behaviors Using Path And Residing Time displaY (PARTY) - Sookhanaphibarn, Kingkarn; Thawonmas, Ruck; Rinaldo, Frank; Chen, Kuan-Ta (International Journal of Virtual Reality, 2013)
Spatiotemporal data displayed in a spatial layout are not the best visualization for finding similarities of visitor paths and extracting patterns of visitor interest to placed items. A challenging problem is the visual analytics of circulation patterns in varying layouts commonly found in a museum with many exhibition rooms. This paper proposes a layout-independent visualization approach to represent a visitor path and his/her time spent residing near the closest item. In this approach, we encode a time interval residing in an item boundary into a color-shaded line segment. Color shade is used as an indicator to the proximity distance to the nearest item. The length of a segment is in proportion to the total time spent in the layout. The time segment is placed in the row corresponding to its item boundary. A path of visited items is illustrated by connecting the time segments with vertical lines. The resulting visualization technique, called Path And Residing Time displaY (PARTY), enables users to find trends of circulation behaviors in a consistent fashion regardless of the targeted layout. We demonstrate the effectiveness of PARTY on two datasets: one showing circulation behaviors of visiting styles in a 3D virtual museum and the other showing a flow of people escaped from an explosion in a building. PARTY is applicable for analyzing data in real and virtual spaces. While the focus of this paper is to apply PARTY to discovering circulation patterns in museums or art galleries, the utilization of this approach covers also visual analytics of customer circulation in a number of environments (e.g. convenient store, department store, World’s Fair, etc.). PARTY provides useful information about the number of visitors to items, flow patterns, crowded areas, items not visited, and other aspects of visitor behaviors.